2020
DOI: 10.1093/ejcts/ezaa444
|View full text |Cite
|
Sign up to set email alerts
|

MitraClip: a word of caution regarding an all too liberal indication and delayed referral to surgery in case of failure

Abstract: OBJECTIVES Although indications for the MitraClip are becoming increasingly liberal, the number of patients requiring valve surgery after an insufficient outcome of the procedure is growing. Referral to surgery is, however, frequently delayed. During this time, the patients often deteriorate. We retrospectively analysed patients before MitraClip implantation and after mitral valve surgery. METHODS A total of 49 patients who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Despite the higher STS-PROM and frequency of prior cardiac operations, the 1-year mortality rate was 21%, which compares favorably with other reports in the literature, where 1-year mortality ranges from 26.5% to 41%. 9 , 15 , 17 The 1-year mortality observed in the current study is comparable to the 1-year mortality of 23.1% after isolated TEER. 3 These results suggest that mitral valve surgery following failed TEER is a viable option even in patients with previous cardiac surgery.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Despite the higher STS-PROM and frequency of prior cardiac operations, the 1-year mortality rate was 21%, which compares favorably with other reports in the literature, where 1-year mortality ranges from 26.5% to 41%. 9 , 15 , 17 The 1-year mortality observed in the current study is comparable to the 1-year mortality of 23.1% after isolated TEER. 3 These results suggest that mitral valve surgery following failed TEER is a viable option even in patients with previous cardiac surgery.…”
Section: Discussionsupporting
confidence: 70%
“…The rate of tricuspid valve repair was higher than in previous studies. 7 , 9 , 15 , 17 There is considerable controversy on the influence and benefit of tricuspid valve surgery at the time of mitral valve surgery. In the CUTTING-EDGE registry, severe tricuspid regurgitation was associated with increased 1-year mortality after mitral valve surgery for failed TEER, 9 but a recent Cardiothoracic Surgery Network trial showed no survival benefit when tricuspid repair was done during mitral repair surgery, with an increased rate of pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, almost half of the patients are alive after 15 years. Mitral valve repair is one of the few remaining primary cardiosurgical procedures and it will remain in our hands as long as we are able to provide a reliable, stable and long-lasting anatomical repair surpassing the results of any interventional strategy [26][27][28][29][30]. Luckily, the complexity of the mitral valves plays into our cards in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…There are varying reports on the time frames between the MitraClip procedure and surgery: Mkalaluh et al 15 report median of 45 days and in-hospital mortality of 33.3%, Melillo et al 16 median of 330 days with an in-hospital mortality of 15% and overall mortality of 26.5%, and Ostovar et al 22 30 days' mortality 26.5% and 1-year mortality of 59.2%.…”
Section: Discussionmentioning
confidence: 99%